Unburdening the Constitution: What Has the Indian Constitution Got to Do with Private Universities, Modernity and Nation States? - DAM, Shubhankar (Institutional Knowledge at Singapore Management University, 2006)
This article critically analyses the decision of the Indian Supreme Court in Yashpal and another v. State of Chhattisgarh and others holding the establishment of private universities as unconstitutional. Swayed by the overwhelmingly irresponsible character of the respondent universities, the Supreme Court innovated constitutional arguments to uphold the claims of the petitioners. While intuitively correct in the context of the immediate facts, the judgment, when analysed in the abstract, reveals the self-inflicted harm it has the potential to cause. The judgment is technologically regressive: it fails to account for the emerging trends in education, especially those related to the use of technology and in particular about the emergence of e-education. It is also unconstitutional: it purports to add grounds for judicial review of primary legislation that agreeably is a constituent rather than an adjudicative act. Finally, it is backward looking: it proposes to reintroduce a moralizing rhetoric in the conduct of education, thereby, paving way for poorer educational standards in India. Underlying these distinct inadequacies is a common inability of the Supreme Court to de-link the university as a project of modernity from its status as the ideological apparatus of the nation-state. Universities, for the Indian Supreme Court, are still an embodiment of the popular will and, therefore, incapable of being appropriated. [PUBLICATION ABSTRACT]